Diponegoro international journal of business - Universitas Diponegoro. Departemen Manajemen (Department of Management, Faculty of Economics and Business, Diponegoro University, 2018)
Empirical issues related to business studies including marketing management, finance management, operation management, human resource management, innovation management, knowledge management, organizational behavior, organizational development, change management, international business, and Islamic business.
Keywords: Business enterprises : Indonesia : Periodicals; Business enterprises; Commerce; Economic history; Indonesia : Commerce : Periodicals; Indonesia : Economic conditions : Periodicals; Indonesia